Comparative analysis of effort tolerance between national level and professional road cyclists: A psychological approach - Pirlot, T.; Scholler, V.; Grappe, F.; Baron, B.; Pageaux, B.; Groslambert, A. (Journal of Science and Cycling, 2024)
Cycling, as a sport, demands not only physical prowess but also a profound understanding of the psychological factors that influence performance (Ouvrard et al., 2019). Among these factors, effort tolerance and pain management stand out as a crucial determinant of success in competitive cycling. The aim of the present study seeks to elucidate the disparities in effort tolerance between national level and professional road cyclists. By examining various psychological variables such as perceived exertion, pain perception, pleasure, motivational factors, and electroencephalography responses, we aim to uncover the nuanced differences that underpin the performance disparities observed in these two cohorts. Eleven amateur and 11 professional cyclists participated in a maximal graded test until exhaustion and a 'Finish Race Test'. This test was designed to simulate the final portion of a cycling race, aiming to evaluate both psychological and physiological responses to high-intensity effort. The ANOVA test revealed a significance group effect for relative MAP but not for maximal oxygen uptake. During the test, the relative body mass PO (W.kg-1) was significantly higher for the PRO nevertheless the relative effort (%MAP) was not different between the both groups. PRO revealed a higher mean RPE in comparison to AM group but also for the quads pain and the pleasure was significantly lower for the PRO than AM. Higher neural efficiency was found for the PRO compared to AM. Compared to amateurs, pros tolerate higher levels of effort and pain with a lower neural efficiency.